2020
DOI: 10.1002/2050-7038.12355
|View full text |Cite
|
Sign up to set email alerts
|

Continuous finite‐time control of four‐leg inverter through fast terminal sliding mode control

Abstract: Summary A favorable option to supply unbalanced loads and provide the neutral wire is the four‐leg inverter. Controllers with high robustness and dynamic response should be used to adjust the inverter load voltages for unknown, unbalanced, and nonlinear loads. Sliding mode controls (SMCs) have a simple structure, good robustness against model parameter uncertainties, and desirable transient response. However, chattering phenomena, variable switching frequency, and error convergence to the operating point on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…From ( 11) and ( 12), it can be concluded that x 2 equals to d(x 1 )/dt. The sliding surface is expressed in (13).…”
Section: Dual-sliding Mode Control Methodsmentioning
confidence: 99%
“…From ( 11) and ( 12), it can be concluded that x 2 equals to d(x 1 )/dt. The sliding surface is expressed in (13).…”
Section: Dual-sliding Mode Control Methodsmentioning
confidence: 99%
“…Non-singular terminal sliding-mode control (NTSMC) approach with a nonlinear sliding surface has been adopted for high requirement on a DC-DC buck converter (Pichan et al, 2020;Yang et al 2013;. In this method, the time taken to reach the desired set point from any initial states under the disturbances is guaranteed to be a finite time, so output voltage in DC-DC buck converter will reach the desired voltage within time required.…”
Section: Introductionmentioning
confidence: 99%
“…The use of inverter-based DGs is one of the best solutions to compensate for the above-mentioned issues, because they can easily cope with unbalanced networks. Several types of inverter topologies are introduced to provide a neutral wire in islanded mini-grids that are presented extensively in the literature [2,[7][8][9]. The three-phase four-leg voltage source inverter (VSI) is the best topology for providing the neutral wire due to the proper operation to supply balanced output voltages even under severe unbalanced load conditions.…”
Section: Introduction 1| Motivationmentioning
confidence: 99%